HUKUM DAN MASYARAKAT - Tuti Haryanti (IAIN Ambon, 2017)
The existence of law in community is most urgent, since the laws regulate the human behavior. Law cannot be separated from community, and otherwise, since in addition to the law have passive function, the law have also active function in controlling any individual actions and always bringing the community into a planned change. The law applicable in community basically come from the community itself and also intentionally burdened upon it, so that the problem/conflict can be minimized. The law applicable should always pay attention to the juridical rules, philosophical principle, the utilities/sociology norms so it does not conflict with the values of life in society. The laws made in community has goal to create peace, tranquility, and order in the community as well as providing the legal certainty. The law objective can be felt in comprehensive in community, if the law can function in community. Thus, the law and community has very significant correlation. The community without law, there will be chaos and arbitrary action, and otherwise the law without community, then the law does not mean at all. Keywords: legal function, community